2019
DOI: 10.1111/puar.13115
|View full text |Cite
|
Sign up to set email alerts
|

Thick Red Tape and the Thin Blue Line: A Field Study on Reducing Administrative Burden in Police Recruitment

Abstract: Police departments struggle to recruit officers, and voluntary drop-off of candidates exacerbates this challenge. Using four years of administrative data and a field experiment conducted in the Los Angeles Police Department, the authors analyze the impact of administrative burden on the likelihood that a candidate will remain in the recruitment process. Findings show that reducing friction costs to participation and simplifying processes improve compliance, as behavioral public administration would predict. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…In fact, these results suggest that burden could be potentially reduced in many programs and still increase favorability, if attention were called to it. While several other articles in this symposium highlight the importance of burdens for the attitudes and behaviors of clients and public sector applicants (see Christensen et al ; Fox, Feng, and Stazyk ; Hattke, Hensel, and Kaluza ; Linos and Riesch ), our study highlights the importance of understanding the way in which administrative burden shapes citizen attitudes toward programs. This is important for the politics of program reform and funding.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…In fact, these results suggest that burden could be potentially reduced in many programs and still increase favorability, if attention were called to it. While several other articles in this symposium highlight the importance of burdens for the attitudes and behaviors of clients and public sector applicants (see Christensen et al ; Fox, Feng, and Stazyk ; Hattke, Hensel, and Kaluza ; Linos and Riesch ), our study highlights the importance of understanding the way in which administrative burden shapes citizen attitudes toward programs. This is important for the politics of program reform and funding.…”
mentioning
confidence: 60%
“…Moreover, integrating the findings of other articles in the symposium provides some interesting avenues for future research looking at how administrative burden influences public employees. For example, Linos and Riesch () find that administrative burden embedded in the selection process affects the recruitment of public employees and leads to lower levels of applicant retention. Building from this, our study provides reason to think that information about the burdens embedded in a program may affect recruitment and retention by influencing how those at the front lines view a program and the clients it serves.…”
Section: Discussionmentioning
confidence: 99%
“…Research into bureaucratic red tape has expanded our knowledge on a variety of topics, including organizational effectiveness (e.g., Pandey, Coursey, and Moynihan ), public and private sector specifics (e.g., Pandey and Kingsley ), managerial alienation (e.g., DeHart‐Davis and Pandey ), personnel recruitment (e.g., Linos and Riesch ), and career intentions (e.g., Hattke, Vogel, and Znanewitz ). The few investigations into the consequences of red tape in citizen‐state interactions (e.g., Christensen et al ; Moynihan and Herd ; Scott and Pandey ; Tummers et al ) have demonstrated that it delays the delivery of services (Bozeman, Reed, and Scott ) and imposes administrative burdens on citizens (Herd et al ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…If so, future research should examine public employees' emotional responses to directives they receive from their superiors—perhaps in conjunction with their own cognitive resources—and examine how they affect compliance with those directives. Furthermore, Linos and Riesch () expand on our results and show that another way to motivate compliance is to simplify processes. Clearly our study does not cover the entire universe of situations that motivate public employees to rebel.…”
Section: Administrative Lessonsmentioning
confidence: 58%
“…As other articles in this symposium (e.g., Christensen et al ; Hattke, Hensel, and Laucza ; Keiser and Miller ; Linos and Riesch ) illustrate, the scope of possible behavioral microfoundations is quite broad, and to address all possible ones is beyond the scope of any single article. To begin the process of parsing out administrative behavior, we focus on O'Leary's insights into how guerrilla government action is processed through bureaucratic politics, ethics, and organization and management.…”
mentioning
confidence: 98%